An Application of the VECM Model to Study the Long-term Relationship between Export and Comparative Advantages Pattern in Poland - Salamaga, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents the dynamic relationship and pattern between export and comparative advantages in Poland. The basic tool used for this study is vector autoregression models. For a more detailed identification of the dynamic interactions between the variables, the results of the impulse response functions and forecast error variance decomposition are analysed. The results provide a benchmark for determining the phase of economic development according to the Ozawa’s theory of dynamic comparative advantages. The important part of this theory applies to the long-term relationship between export and revealed comparative advantage indexes of goods that have a different share of the production factors. Data from the Central Statistical Office covering the period from the first quarter of 2002 to the fourth quarter of 2012 were used for the calculations.